Societal participation in the development of orphan drugs: a systematic review - Akodad, Sanae; De Smedt, Delphine; Stevens, Hilde (Frontiers in Medicine, 2025)
The development of orphan drugs (ODs) remains constrained by structural barriers, including limited scientific knowledge, high clinical uncertainty, and fragile commercial incentives. In parallel, an alternative ecosystem has emerged in which non-commercial societal actors (patients, advocacy groups, and philanthropic entities) contribute to the design, evaluation, and dissemination of therapies for rare diseases. This systematic review provides the first structured synthesis of empirical evidence on societal participation in OD development, with a specific focus on neuromuscular and neurodegenerative disorders. Twenty-one peer-reviewed studies were included, spanning a range of designs from case reports to stakeholder surveys. A functional typology of societal roles was developed, identifying four primary modalities: Initiator, Accelerator, Translator, and Monitor. Societal actors contributed to early-stage funding, trial co-design, regulatory engagement, dissemination, and patient preference studies. Their involvement was associated with accelerated development timelines, improved recruitment and retention, enhanced endpoint relevance, increased public literacy, and the emergence of new ethical standards. However, critical tensions remain. The review identifies persistent gaps in representation, risks of tokenism and instrumentalization, blurred governance boundaries, and a lack of longitudinal evaluation frameworks. Although initiatives like EUPATI and IMI PREFER have begun addressing these challenges, further work is required to ensure inclusive, evidence-based, and structurally supported societal engagement. As the European Union Health Technology Assessment Regulation (EU HTAR) reshapes decision-making frameworks, societal participation is no longer peripheral but integral to regulatory legitimacy and therapeutic relevance. Realizing its full potential requires moving beyond anecdotal engagement toward durable, transparent, and evaluable participatory models.